Molecular Profiling and Pathological Evaluation of Bovine Papillomavirus-1 in Cattle in Al-Sharkia, Egypt - Ayman Ahmed Shehata; Elshaima Mohamed Fawzi; Mahran Mohamed Abd El-Emam; Shimaa M. Abdullah; Wafaa Hassan; Asmaa lbrahim Abdelaziz Zin Eldin; Hend E. M. Elsheikh (Veterinary Medicine International)
Bovine papillomatosis virus (BPV) is a prevalent cutaneous oncogenic viral disease in cattle, causing economic losses due to reduced milk production, poor carcass quality, and hide damage. Despite BPV’s economic significance, molecular information on current strains, genetic relationships, and origins in Egypt is limited, with most studies focusing on electron microscopy and histopathological analysis. The study aimed to genetically analyze BPV-1 circulation in Al-Sharkia, Egypt, and characterize viral strains compared with local and global papillomaviruses isolates. A total of 27 crossbred cattle with clinical symptoms of papillomatosis, such as wart-like lesions on various body parts, were examined. The collected tissue samples underwent histological analysis, revealing typical benign neoplasms such as hyperkeratosis and koilocytes. Polymerase chain reaction (PCR) confirmed the presence of BPV-1 in all samples, with partial amplification of the L1 gene. Sequencing and phylogenetic analysis of three representative samples indicated high similarity to BPV-1 strains from Egypt, Iraq, Turkey, and Belgium, suggesting livestock trading may play a role in disease transmission. The isolates were found to be linked to equine Delta papillomavirus 4 (DPV4) strains, indicating cross-species transmission between cattle and equines. The study marks one of the first reports of BPV-1 infection in cattle in Al-Sharkia, providing crucial molecular insights into Egypt’s circulating strains and emphasizing the need for stronger biosecurity protocols in animal trading.